SCANNING FACTORS AFFECTING COMPARATIVE ADVANATAGE OF AGRICULTURAL COMMODITIES IN PAKISTAN - Imran Ahmad; Abdul Saboor; Safdar Hussain; Fayyaz ul Hassan (International Journal of Contemporary Issues in Social Sciences, 2024)
The present article intends to systematically review the key factors that defines the determinants of agricultural exports across various crop-producing areas of Pakistan. It involves a comprehensive survey through self-administered interviews and questionnaires to different stakeholders like farmers, processors, exporters and administration. The questions were designed across lines of marketing, value addition, production, export, branding and government support and initiatives. The findings reveal that the variables; production, producer price, input prices, export prices, marketing and value addition and government support have a significant positive impact on exports of agricultural commodities in Pakistan.. The current analysis shows that the expansion of agriculture exports is a necessary precondition for the wider development of industry and the economy. Multiple scholarly entities and classes have observed the crucial role of these elements in determining agricultural exports. Government policy makers will have a better understanding of the factors influencing Agri-exports and how they relate to economic growth and trade enhancement of Pakistan.